Menerima, Bertahan, dan Bangkit: Makna Stigma Sosial dalam Kehidupan Orang Tua dari Anak Berkebutuhan Khusus - Al Fikroni, Zamakhsyari Firdaus; Challi, Aryu; Ainiyah, Hilma; Sugiarti, Lucia Rini; Suhariadi, Fendy (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study aims to understand the experiences of parents of children with special needs (CWSN) in facing social stigma originating from their surrounding environment, including both the general public and close relationships such as family and friends. This research employs a qualitative approach using a phenomenological method, involving three participants with diverse child backgrounds and social environments. Data were collected through in depth interviews and analyzed using data reduction techniques. The results show that the forms of social stigma experienced are not only explicit, such as direct labeling, but also appear in subtle, often unconscious forms, known as microaggressions. The most painful stigmas often come from those closest to the parents, who are expected to provide emotional support. Nevertheless, the participants demonstrated the ability to build psychological resilience through self reflection, social support, and the use of social media as a space for empowerment. These findings affirm that the experience of confronting stigma, when supported appropriately, can trigger the formation of a stronger identity as parents of CWSN and create space for positive psychological growth.